Unlocking muscle recovery: The therapeutic potential of microRNAs in accelerating muscle regeneration - Mohammad Reza Zabihi; Mohammad Akhoondian (Journal of Sports and Rehabilitation Sciences)
Muscle tears are common in sports and can lead to significant impairments if not properly diagnosed and treated. Magnetic resonance imaging (MRI) is widely regarded as the gold standard for diagnosing these injuries. The microRNAs (miRNAs) have recently been identified as key muscle repair and regeneration regulators. This study aims to investigate specific miRNAs' role in muscle tears' recovery process and explore their therapeutic potential in enhancing muscle regeneration. A comprehensive review was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Relevant studies were identified through an extensive database search, including PubMed, Scopus, and Web of Science. The inclusion criteria focused on studies examining miRNAs' roles in muscle regeneration. Data on miRNA expression patterns, their effects on muscle repair mechanisms, and potential therapeutic applications were extracted. Quality assessment of the studies was performed using the Cochrane Risk of Bias Tool. The findings indicate that miR-224 plays a crucial role in the interaction between myoblasts and macrophages, influencing the inflammatory environment necessary for muscle recovery. The miR-133 and miR-1 were found to regulate cell proliferation and differentiation, while miR-206 was essential for satellite cell activation and neuromuscular synapse regeneration. Inhibition of miR-224 and modulation of miR-133 was associated with improved muscle repair and reduced fibrosis. The miRNAs such as miR-224, miR-133, miR-1, and miR-206 play pivotal roles in muscle regeneration, offering potential therapeutic targets for enhancing recovery from muscle injuries. The miRNA-based therapies could improve rehabilitation outcomes, particularly in preventing fibrosis and promoting efficient muscle repair.